Ablasio retina rhegmatogen bilateral: sebuah laporan kasus - Amicipta Sanjaya; Ari Andayani; I Made Agus Kusumadjaja (Intisari Sains Medis, 2022)
Background: Rhegmatogenous retinal detachment in children is rare, accounting for less than ten percent of all rhegmatogenous retinal detachments. While the majority of retinal detachments in the adult population are associated with posterior vitreous detachments, pediatric rhegmatogenous retinal detachments are often associated with trauma or an underlying congenital abnormality, although in some cases they are associated with idiopathic conditions. Case Description: A 16-year-old male patient complained about blurry vision in the right eye in the last 6 months and in the left eye in the last 5 months. Ophthalmology examination in the right eye found an inferior retinal detachment (+) at 3-9 o’clock, multiple breaks at 7-9 hours, PVR grade C, subretinal fibrosis (+), traction (+), macula off, RM (-). Meanwhile, ophthalmology examination in the left eye found an inferior retinal detachment in the left eye (+) at 3-9 o’clock, break at 5 o'clock, PVR grade C, traction (+), RM (+). The patient underwent pars plana vitrectomy in both eyes and the patient experienced an increase in visual acuity after surgery on both eyes. Conclusion: This case describes a healthy adolescent male with bilateral rhegmatogenous retinal detachment secondary to spontaneous non-traumatic retinal dialysis. The Pars Plana Vitrectomy (VPP) technique that used in this case could give high final reattachment rate and relatively good functional outcomes. VPP also has the intraocular ability to manipulate tissues and reduce immediate vitreous traction.   Latar Belakang: Ablasio retina rhegmatogenous pada anak-anak jarang terjadi, terhitung kurang dari sepuluh persen dari semua ablasio retina rhegmatogen. Sementara sebagian besar ablasio retina pada populasi orang dewasa terkait dengan ablasio vitreous posterior, ablasio retina hegmatogen pediatrik sering kali berhubungan dengan trauma atau kelainan kongenital yang mendasari, walaupun pada beberapa kasus didapatkan dengan kondisi idiopatik. Laporan Kasus: Pasien laki-laki berusia 16 tahun mengeluhkan penurunan pengelihatan pada mata kanan sejak 6 bulan sebelumnya dan pada mata kiri 5 bulan sebelumnya. Pemeriksaan oftalmologi didapatkan AAR di mata kanan dengan retinal detachment (+) di inferior pada jam 3-9, multiple break pada jam 7-9, PVR grade C, fibrosis subretina (+), traksi (+), macula off, RM (-). Pemeriksaan pada mata kiri didapatkan retinal detachment di mata kiri (+) di inferior pada jam 3-9, break pada jam 5, PVR grade C, traksi (+), RM (+). Pasien menjalani vitrektomi pars plana pada kedua mata dan pasien mengalami peningkatan tajam penglihatan setelah dilakukan tindakan operasi pada kedua mata. Kesimpulan: Kasus ini menjelaskan remaja laki-laki sehat dengan bilateral ablasio retina rhegmatogen sekunder akibat retinal spontan non-trauma dialisis. Teknik Vitrektomi Pars Plana (VPP) digunakan pada kasus ini dan mampu memberikan tingkat attachment akhir yang tinggi dan hasil fungsional yang relatif baik serta kemampuan intraokular untuk memanipulasi jaringan dan mengurangi traksi vitreous secara langsung.